2022
DOI: 10.2147/ibpc.s374674
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Blood Pressure Control Among Hypertensive Outpatients Attending a Tertiary Cardiovascular Hospital in Tanzania: A Cross-Sectional Study

Abstract: Background: Notwithstanding the availability of effective treatments, asymptomatic nature and the interminable treatment length, adherence to medication remains a substantial challenge among patients with hypertension. Suboptimal adherence to BP-lowering agents is a growing global concern that is associated with the substantial worsening of disease, increased service utilization and healthcare cost escalation. This study aimed to explore medication adherence and its associated factors among hypertension outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 119 publications
1
6
0
1
Order By: Relevance
“…The outcome established that 70.6% of patients <65 years attained blood pressure values of <140/90 mm Hg compared to 66.3% among patients ≥65 years [ 15 ]. Similar results were also observed in the study by Pallangyo et al that showed groups of ≤60 vs. >60 years displaying similar adherence of 76.8% vs. 77.1%, respectively [ 16 ]. This is inconsistent with the current research that showed that most of the patients aged 65 years reached their SBP target compared to the subgroup of <65 years.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The outcome established that 70.6% of patients <65 years attained blood pressure values of <140/90 mm Hg compared to 66.3% among patients ≥65 years [ 15 ]. Similar results were also observed in the study by Pallangyo et al that showed groups of ≤60 vs. >60 years displaying similar adherence of 76.8% vs. 77.1%, respectively [ 16 ]. This is inconsistent with the current research that showed that most of the patients aged 65 years reached their SBP target compared to the subgroup of <65 years.…”
Section: Discussionsupporting
confidence: 89%
“…In other words, men were more compliant with antihypertensive therapy compared to women [ 22 ]. Conversely, Pallangyo et al documented that males recorded similar adherence to females (75.6 vs. 77.6%) [ 16 ]. Furthermore, patients treated in primary care settings showed a significant reduction in SBP compared to patients treated in secondary and tertiary care settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volume 3 | Issue 3 | 2022 2 http://ijcimr.org/ and high blood pressure (6,7). In addition, it has been determined that weight gain increases the risk of high blood pressure, even if it remains within the normal BMI limits (8).…”
Section: Studies Have Found a Relationship Between High Body Mass Ind...mentioning
confidence: 99%
“…A pesar de la disponibilidad de tratamientos efectivos, la naturaleza asintomática de la enfermedad y la interminable duración del tratamiento, la adherencia a la medicación sigue siendo un desafío importante entre los pacientes con hipertensión. Según la OMS, más de la mitad de las personas con hipertensión interrumpen sus antihipertensivos por completo dentro del primer año del diagnóstico y como máximo la mitad de los que continúan con los medicamentos consumen ≥80% de sus regímenes prescritos 2 .…”
Section: Introductionunclassified